2016
DOI: 10.1111/acem.13000
|View full text |Cite
|
Sign up to set email alerts
|

Extravasation Risk Using Ultrasound‐guided Peripheral Intravenous Catheters for Computed Tomography Contrast Administration

Abstract: Objective Ultrasound guided intravenous catheter (USGIV) insertion is increasingly being used for administration of intravenous contrast for computed tomography (CT) scans. The goal of this investigation was to evaluate the risk of contrast extravasation among patients receiving contrast through USGIV catheters. Methods A retrospective observational study of adult patients who underwent a contrast-enhanced CT scan at a tertiary-care emergency department during a recent 64-month period was conducted. The unad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…No statistically significant heterogeneity was detected with a Chi-square value of 0.89 ( P = 0.35) and an I 2 of 0%. The effect of gender was also emphasized in a multivariate logistic regression by Rupp et al 40 Being a female was associated with an increased risk of extravasation, as indicated by the adjusted odds ratio of 1.8 (95% CI: 1.1–2.9).…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…No statistically significant heterogeneity was detected with a Chi-square value of 0.89 ( P = 0.35) and an I 2 of 0%. The effect of gender was also emphasized in a multivariate logistic regression by Rupp et al 40 Being a female was associated with an increased risk of extravasation, as indicated by the adjusted odds ratio of 1.8 (95% CI: 1.1–2.9).…”
Section: Resultsmentioning
confidence: 94%
“…Among the citations that had data on the relevant outcomes, there was one randomized control trial, 37 one pseudo-randomized trial, 36 one quasi-experimental trial, 19 and one pre-post study, 31 with the remainder being cohort 9 , 23 , 26 , 27 , 28 , 34 , 40 , 42 or case series designs. 38 , 39 , 41 Studies other than clinical trials were included when they related to a different outcome, population of interest or intervention.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations